The optimized acupuncture treatment for neck pain caused by cervical spondylosis: a study protocol of a multicentre randomized controlled trial - Liang, Zhao-Hui (BioMed Central, 2012)
BACKGROUND: Neck pain is one of the chief symptoms of cervical spondylosis (CS). Acupuncture is a well-accepted and widely used complementary therapy for the management of neck pain caused by CS. In this paper, we present a randomized controlled trial protocol evaluating the use of acupuncture for CS neck pain, comparing the effects of the optimized acupuncture therapy in real practice compared with sham and shallow acupuncture. METHODS/DESIGN: This trial uses a multicentre, parallel-group, randomized, sham acupuncture and shallow acupuncture, controlled single-blind design. Nine hospitals are involved as trial centres. 945 patients who meet inclusion criteria are randomly assigned to receive optimized acupuncture therapy, sham acupuncture or shallow acupuncture by a computerized central randomization system. The interventions past for 4 weeks with eight to ten treatments in total. The group allocations and interventions are concealed to patients and statisticians. The Northwick Park Neck Pain Questionnaire (NPQ) is used as the primary outcome measure, and the McGill Pain Questionnaire (MPQ) and The Short Form (36) Health Survey (SF-36) are applied as secondary outcome measures. The evaluation is performed at baseline, at the end of the intervention, and at the end of the first month and the third month during follow-up. The statistical analyses will include baseline data comparison and repeated measures of analysis of variance (ANOVA) for primary and secondary outcomes of group and time differences. Adverse events (AEs) will be reported if they occur. DISCUSSION: This trial is a multicentre randomized control trial (RCT) on the efficacy of acupuncture for CS neck pain and has a large sample size and central randomization in China. It will strictly follow the CONSORT statement and STRICTA extension guideline to report high-quality study results. By setting the control groups as sham and shallow acupuncture, this study attempts to reveal the effects of real acupuncture versus placebo or non-classic acupuncture treatment and evaluate whether classic Chinese medical acupuncture is effective on CS neck pain. This study will provide evidence for the effects of acupuncture on CS neck pain. TRIAL REGISTRATION: Chinese Clinical Trial Registry: ChiCTR-TRC-00000184.